Effect of transauricular nerve stimulation on perioperative pain: a single-blind, analyser-masked, randomised controlled trial. (April 2023) - Patel, Amour B.U.; Bibawy, Phillip P.W. M.; Althonayan, Juri Ibrahim M.; Majeed, Zehra; Gan, Weng L.; Abbott, Tom E.F.; Ackland, Gareth L.
Abstract: Background: Activation of central autonomic pathways, including those regulating the arterial baroreflex, might reduce acute pain. We tested the hypothesis that transcutaneous auricular nerve stimulation (TAN) reduces pain after orthopaedic trauma surgery through autonomic modulation. Methods: A total of 86 participants aged >18 yr were randomly assigned to 50 min of either sham or active bilateral TAN, undertaken before, and again 24 h after, surgery for orthopaedic trauma. The primary outcome was absolute change in pain 24 h postoperatively, comparing the 100 mm visual analogue scale (VAS) before and after TAN. Secondary outcomes included the minimal clinically important difference in pain (>10 mm increase or reduction in VAS) before/after surgery, using intention-to-treat analysis. Holter monitoring, the analysis of which was masked to allocation, quantified autonomic modulation of heart rate. Results: From June 22, 2021 to July 7, 2022, 79/86 participants (49 yr; 45% female) completed TAN before and after surgery. For the primary outcome, the mean reduction in VAS was 19 mm (95% confidence interval [CI]: 12–26) after active TAN ( n =40), vs 10 mm (95% CI: 3–17) after sham TAN ( n =39; P =0.023). A minimally clinically important reduction in postoperative pain occurred in 31/40 (78%) participants after active TAN, compared with 15/39 (38%) allocated to sham TAN (odds ratio 5.51 [95% CI: 2.06–14.73]; P =0.001). Only active TAN increased heart rate variability (log low-frequency power increased by 0.19 ms 2 [0.01–0.37 ms 2 ]). Prespecified adverse events (auricular skin irritation) occurred in six participants receiving active TAN, compared with two receiving sham TAN. Conclusion: Bilateral TAN reduces perioperative pain through autonomic modulation. These proof-of-concept data support a non-pharmacological, generalisable approach to improve perioperative analgesia.